Β-Amyrin Synthase1 Controls the Accumulation of the Major Saponins Present in Pea (Pisum sativum). (7th April 2021) - Vernoud, Vanessa; Lebeigle, Ludivine; Munier, Jocelyn; Marais, Julie; Sanchez, Myriam; Pertuit, David; Rossin, Nadia; Darchy, Brigitte; Aubert, Grégoire; Le Signor, Christine; Berdeaux, Olivier; Lacaille-Dubois, Marie-Aleth; et al.
Abstract: The use of pulses as ingredients for the production of food products rich in plant proteins is increasing. However, protein fractions prepared from pea or other pulses contain significant amounts of saponins, glycosylated triterpenes that can impart an undesirable bitter taste when used as an ingredient in foodstuffs. In this article, we describe the identification and characterization of a gene involved in saponin biosynthesis during pea seed development, by screening mutants obtained from two Pisum sativum TILLING (Targeting Induced Local Lesions IN Genomes) populations in two different genetic backgrounds. The mutations studied are located in a gene designated PsBAS1 ( β-amyrin synthase1 ), which is highly expressed in maturing pea seeds and which encodes a protein previously shown to correspond to an active β-amyrin synthase. The first allele is a nonsense mutation, while the second mutation is located in a splice site and gives rise to a mis-spliced transcript encoding a truncated, nonfunctional protein. The homozygous mutant seeds accumulated virtually no saponin without affecting the seed nutritional or physiological quality. Interestingly, BAS1 appears to control saponin accumulation in all other tissues of the plant examined. These lines represent a first step in the development of pea varieties lacking bitterness off-flavors in their seeds. Our work also shows that TILLING populations in different genetic backgrounds represent valuable genetic resources for both crop improvement and functional genomics.